EXTRACTION OF GRAPE SEED OIL BY COLD PRESSING (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Grape seed oil (GSO) is a valuable product in the food, cosmetic, and pharmaceutical industries due to its high content of polyunsaturated fatty acids, antioxidants, and other bioactive compounds. Cold pressing is an effective method for extracting GSO, as it preserves the oil's nutritional quality without the use of heat or solvents. This article reviews the cold pressing method for GSO extraction, highlighting the process, advantages, challenges, and applications of cold-pressed grape seed oil.